Intervertebral infection due to Candida albicans in an intravenous heroin abuser. Issue 6 (June 1988) - Rowe, I F; Wright, E D; Higgens, C S; Burnie, J P
Abstract : A 25 year old woman who had received intravenous heroin over one year previously developed an intervertebral abscess due to infection with Candida albicans. Immunological investigation of this patient showed no evidence of a specific defect in the host response to candida.